A Critical Discourse Analysis on Local Wisdom-Based English Teaching in Vocational Universities: Lecturers' and Students' Insights - Indah Sari; Muthia Damaiyanti; Ching Yi Tien; Ricci Gemarni Tatalia (Jurnal Gramatika, 2024)
Vocational universities play a crucial role in shaping a workforce that is well-prepared for the demands of various industries. They Integrate local wisdom into English teaching and learning brings cultural relevance and a deeper sense of identity to students’ educational experiences. This research aimed at to find out the lecturers and student point of view about the implementation of local wisdom-based English teaching and learning in vocational universities. The research question was how the implement of local wisdom-based English teaching and learning in vocational universities from lecturers and students point of view. It used a descriptive qualitative research by using content analysis. Data were collected by using interview method using validated interview questions. It also was analyzed by using content analysis and social discourse of critical discourse analysis from Fairclough. It shows that there are several lecturers and student perception about implementation of local wisdom-based English teaching and learning in vocational universities such as motivation for students, impact on language proficiency, enhanced student engagement, tailored teaching strategies, challenging in standardization, relevance to local context, facilitating cross-cultural understanding, cultural preservation, community development and professional development.  There are some significances of the research. For the lecturers, this research can give a new paradigm or best practices on how to do the English teaching and learning in vocational universities. For the students, this research can give a new learning process for English learning. At last, for the government, this research can be considered to be policies in education in English teaching and learning.